Higher education in a global society achieving diversity, equity and excellence - Allen, Walter Recharde; Bonous-Hammarth, Marguerite; Teranishi, Robert T. (Robert Takumi), 1974- (Amsterdam ; Boston : Elsevier JAI, 2006)
The "problem of the 21st century" is rapidly expanding diversity alongside stubbornly persistent status and power inequities by race, ethnicity, gender, class, language, citizenship and region. Extensive technological, economic, political and social changes, along with immigration, combine to produce a global community of great diversity and interpenetration. Unfortunately, this global community continues to be fractured by extreme disparities in wealth and power, divided into "haves" and "have-nots." Universities around the globe can play critical roles in economic development and sociocultural exchange. Where different communities interact, overlap, exchange and compete for scarce resources, complex challenges are presented. Current discourse often views difference and diversity as problems; however, a growing scholarship reframes difference and diversity as potential resources.This volume presents research into the consequences of difference and diversity for higher education. An international group of scholars reflects on the challenges and prospects of diversity, difference and inclusion for universities in their respective societies. Various theoretical and empirical perspectives are used to better understand how diverse populations and expectations intersect to influence higher education and societies globally. Diversity and difference are defined broadly to encompass specific national contexts and their particular emphases on race, ethnicity, gender, culture, language, religion, sexual orientation and/or region.We find that around the world, higher and tertiary institutions confront the "diversity imperative" with varying approaches, success and "best practices." This volume identifies challenges and opportunities that diversity poses for higher education. It provides international comparisons of how diversity affects higher education and of the salience and impact of diversity in higher education. It outlines practical, effective strategies for managing diversity in higher education across different societies.
Editor's Welcome / Carol Camp Yeakey -- Preface / Walter R. Allen, Marguerite Bonous-Hammarth, Robert T. Teranishi -- International scientific associations and intercultural dialogue / Alberto Martinelli -- Nigerian universities and the problem of cultural diversity: policy responses and consequences / L. Adele Jinadu -- How to meet the challenge of diversity in the French system of education? / Sarah Esther Ouaja -- Polish universities as a place of study and academic careers: class and gender considerations / Renata Siemieñska -- Diversity in education: the Chinese version / Kai-Ming Cheng -- Diversification in Russian higher education: profiles, foundations and outlooks / Andrey V. Rezaev -- Obstacles to diversity: examining the educational pipeline / Walter R. Allen, Marguerite Bonous-Hammarth, Robert T. Teranishi -- Higher education, "race" and the inclusive society / Peter Ratcliffe -- The diversity challenge: the representation of ethnic minorities in the Dutch educational system / Peary Bru -- Gender diversity in higher education: "the women are fine, but the men are not?" / Florence B. Bonner -- The quest for equity in California higher education: implications for a global society / Robert T. Teranishi -- Institutional change and the transformative potential of the university / Walter R. Allen, Marguerite Bonous-Hammarth, Robert T. Teranishi -- Sticks, stones, and broken bones: rhetoric and reality in the University of Michigan affirmative action cases / Walter R. Allen -- Widening participation in United Kingdom universities: the challenges of achieving race equality / Deborah Phillips, Ian Law, Laura Turney -- Diversity and learning for a pluralistic democracy / Sylvia Hurtado -- Promoting student participation in science, technology, engineering and mathematics careers / Marguerite Bonous-Hammarth -- Sounds and silences: gendered change in higher education institutions in the Commonwealth / Louise Morley -- Challenges and prospects for achieving diversity: the case of South Africa / Hugh Africa -- Affirmative actions and the scheduled castes: access to higher education in India / G.G. Wankhede -- Innovation and diversity: new horizons in higher education / Walter R. Allen, Marguerite Bonous-Hammarth, Robert T. Teranishi -- Who shall be educated? Governmental policy influences on educational opportunity / Carol Camp Yeakey -- Quantitative approaches to measuring student body diversity: some examples and thoughts / Mitchell J. Chang, Erica Yamamura -- Achieving justice and equality in U.S. higher education: an exemplary program to increase the participation of underrepresented students of color / William Trent, Yuqin Gong -- Seeing and being seen: uses of photography to improve campus climate for diversity / Carol Petersen.
"This volume evolves from an international conference in March 2003 at the Rochefeller Foundation Study and Conference Center in Bellagio, Italy"--P. xv.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Education, Higher -- Congresses; Multicultural education -- Congresses; Education and globalization -- Congresses; Organization & management of education; Higher and further education, tertiary education; Education -- General